INVESTMENT IN RESEARCH AND DEVELOPMENT FOR THE ADVANCEMENT OF THE CIRCULAR ECONOMY - Stoimenov, Suzana; Gračanac, Aleksandar; Jakopin, Edvard; Radosavac, Adriana (ACADEMIC REVIEW, 2024)
The development of consciousness and the dynamics of changes in nature and society require adaptation of the way of life in the world, economic activities and the way of using renewable and non-renewable resources in nature. The aim of the study is a comparative analysis of directed investment in the development of the circular economy in the Republic of Serbia and developed countries of the European Union. In the study, an analysis of the dynamics of investments in research and development of the circular economy in developed countries (Sweden, Germany, Denmark, Austria, Belgium, Japan) and in Serbia was carried out and a comparison was made with the average investments in the European Union and the world. Data from the Eurostat database and the World Bank were used for the study, in the period from 2000 to 2020. Based on the data, it was found that in Sweden and Japan, investment in research and development was at the level and higher than 3% of GDP in the period from 2003 to 2020, which is in accordance with the defined rate in the European Union. Investments in research and development at the level of 3% of GDP were achieved in Austria (2014), Denmark (2015) and Germany (2017) until 2020In other countries, investment varied and reached up to 2% of GDP, while in Serbia, investment in research and development in the studied period ranged from 0.30% to 0.82% of GDP, and on average 0.68% of GDP. which is significantly less than the studied EU countries and the average in the world. The progress of the circular economy requires the support of state governments and international financial institutions for greater investment in research and development for the implementation of innovations and technological solutions in the production and preservation of resources and the environment.